(untitled) (Baghdad Science Journal, 2021)
Oily wastewater is one of the most challenging streams to deal with especially if the oil exists in emulsified form. In this study, electrospinning method was used to prepare nanofiberous polyvinylidene fluoride (PVDF) membranes and study their performance in oil removal. Graphene particles were embedded in the electrospun PVDF membrane to enhance the efficiency of the membranes. The prepared membranes were characterized using a scanning electron microscopy (SEM) to verify the graphene stabilization on the surface of the membrane homogeneously; while FTIR was used to detect the functional groups on the membrane surface. The membrane wettability was assessed by measuring the contact angle. The PVDF and PVDF / Graphene membranes efficiency was tested in separation of emulsified oil from aqueous solutions. The results showed that PVDF-Graphene nanofiber membrane exhibited better performance than the plain PVDF nanofiber membrane with average water flux of 210 and 180 L.m-2.h-1, respectively. Both membranes showed high oil rejection with more than 98%.